Tinjauan Kriminologis Terhadap Korupsi Pengadaan Benih Bawang Merah Dikabupaten Malaka: (STUDI PUTUSAN NOMOR 39/PID-SUS-TPK/2023/PN.KPG, PUTUSAN NOMOR 40/PID-SUS-TPK/2023/PN.KPG, PUTUSAN NOMOR 41/PID-SUS-TPK/2023/PN.KPG DAN PUTUSAN NOMOR 42/PID-SUS-TPK/2023/PN.KPG) - Dian Maranatha Fallo; Heryanto Amalo; Darius A. Kian (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Extraordinary Crime is a label given to the crime of corruption. This is because corruption can hamper the economic life of the nation and state. Therefore, the eradication of corruption cannot be handled in the usual way but through an extraordinary handling. Corruption is a serious problem that can threaten the continuity of the Indonesian nation, coupled with the fact that the perpetrators of corruption are officials of government agencies who have a duty to foster and serve the community for the fulfillment of justice and public welfare. One of the easy targets for people who commit corruption, namely officials of government agencies in launching their actions, is the procurement sector of government goods and services. As happened in the procurement of shallot seeds in Malaka Regency in the 2018 fiscal year involving government agency officials and private parties.The problem formulations in this study are: (1) Factors causing corruption in the procurement of government goods and services, namely the procurement of shallot seeds in Malaka Regency (2) The impact of corruption in the procurement of shallot seeds in Malaka Regency (3) Countermeasures to improve the process of procurement of government goods and services in Malaka Regency.The writing of this thesis uses a type of juridical-empirical research with a case approach method, so that it is based on applicable laws and regulations and data obtained in the field. The case approach taken in this research is related to the corruption case of shallot procurement in Malacca Regency in the 2018 fiscal year.The results of the study show that the factors causing corruption in the procurement of shallot seeds in Malaka Regency are the intention of the defendants, the existence of authority and the opportunity for corruption. The impact of corruption in the procurement of shallot seeds in Malaka Regency is a state loss of Rp. 4,770,725,000.00 (four billion seven hundred seventy million seven hundred twenty-five thousand rupiah), not only limited to state losses but also losses felt by the community and government agencies involved in the corruption case of shallot seed procurement, namely the Government Goods / Services Procurement Section at the Regional Secretariat of Malaka Regency and also the Agriculture and Food Security Office of Malaka Regency. Therefore, efforts to eradicate corruption in the procurement of goods and services of the Malaka district government are not only carried out by the government alone, but also involve the active role of the community in preventing corruption in the government goods/services procurement sector and also countermeasures involving cooperation between the Malaka district government and the Malaka district police.